A model of inflation consistent with Planck 2018 and BICEP/Keck data - Li-Yang Chen; Hongwei Yu; Puxun Wu (European Physical Journal C: Particles and Fields)
Abstract We establish a phenomenological inflation model in this paper and find that the predicted values of the spectral index and the tensor-to-scalar ratio are well consistent with the results from the Planck 2018 survey and the BICEP/Keck array measurement, significantly improving the theoretical precision in describing the early universe’s inflationary process. After inflation, we find that preheating can occur from the tachyonic instability or the parametric resonance, which depends on the value of one of model parameters.